Ответы и объяснения

Лучший Ответ!
2013-11-16T07:29:44+00:00
((3 1/3 + 5 7/9) * 2 1/4 -1 1/5 *( 3 5/6 - 7/12 + 9 7/8)) * 16/39 = 173 7/13
1) 3 1/3+ 5 7/9= 3 3/9 + 5 7/9=8 10/9
2) 8 10/9 * 2 1/4=  720/9 * 9/4 (сокращаем 720 и 4 на 4, сокращаем 9 и 9 на 9)=180
3) 3 5/6 - 7/12= 3 10/12 - 7/12= 3 3/12= 3 1/4
4) 3 1/4+ 9 7/8= 3 2/8 + 9 7/8 = 12 9/8= 13 1/8
5) 1 1/5 * 13 1/8=  6/5 * 105/8 (сркращаем 6 и 8 на 2, сокращаем 105 и 5 на 5)=63/4=15 3/4       105:5=21
6) 15 3/4 * 16/39= 63/4 * 16/39= 84/13= 6 6/13
7)180 - 6 6/13= 179 13/13 - 6 6/13= 173 7/13
   Надеюсь правильно))